부산 광안대교 하부 퇴적토 오염도 평가 - 임준혁(Jun Heok Lim); 김동수(Dong Soo Kim); 이태윤(Tae Yoon Lee); 김석구(Seog Ku Kim); 안재환(Jae Whan Ahn); 강성원(Sung Won Kang); 윤상린(Sang Leen Yun); 이정우(Jung Woo Lee); 이제근(Jea Keun Lee) (Daehan hwan'gyeong gonghag hoeji, 2013)
In this study, physical properties and heavy metal contents of sediments obtained from the bottom of Gwangan bridge were measured to determine pollution level of the sediments. From the results of the oxide contents of the sediments, $SiO_2$ was decreased as the sampling points became more distant from the stream of river. On the contrary, CaO showed opposition aspect to $SiO_2$. Ignition loss of sediments ranged from 7.2 and 14.3% and 0.9 and 5.5% for TOC. For EPA guidelines of ignition loss, all sampling points were classified as heavily polluted areas. When TOC was considered, all areas were classified as lowest effect level except for GW7 where classified as no effect level. All areas were free of heavy metal contamination evaluated by USEPA and Canadian guidelines. However, all areas were classified as heavily contaminated areas due to the high value of ignition loss when USEPA was used. 본 연구는 광안대교 하부의 퇴적토 오염조사를 위해 퇴적토의 기본물성 및 중금속 함량을 측정하였다. 퇴적물 시료의 산화물을 분석한 결과, $SiO_2$와 CaO의 경우 강하구에서 멀어 질수록 $SiO_2$는 증가하고 CaO는 감소하는 경향을 보였다. 강열감량의 경우, 7.2~14.3%의 분포를 보여 비교적 높은 값을 나타내었고 TOC는 0.9~5.5%로 지역에 따라 편차가 큰 것을 알 수 있었다. 이는 USEPA 퇴적물환경기준(비오염, 중간오염, 심한오염)에 따라 심한오염으로 평가되었고, TOC의 경우, 강하구에서 가장 먼 시료채취 지점(GW7)은 영향없음으로 평가되었고 나머지 지역은 최소영향수준으로 평가되었다. 중금속의 경우에는 USEPA와 캐나다 기준으로 평가하였을 때 모두 비오염으로 평가되어 중금속에 대한 오염도는 없는 것으로 평가되었다. 다만, 강열감량의 값이 크기 때문에 USEPA 기준으로 평가할 때 중금속의 오염은 없지만 전체적으로는 심한 오염으로 평가되었다.